WORKPLACE PROGRAM - BECKER K; SPARBER PG (Tufts Archival Research Center, 2007)
Memo to Samuel Chilcote from K. Becker and P. Sparber on behalf of the Tobacco Institute (TI) task group on smoking in the workplace. Asks for approval in order to implement certain parts of pending workplace proposal. Discusses basic points of proposal and questions raised by the TI Executive Committee. Asks for permission to move ahead in additional areas and requests additional funding.